Poetry Vocare - Groves, Adam Staley (punctum books, 2011)
Poetry Vocare is the first collection of poetry published by young American poet A. Staley Groves. A dense fabric of resemblances and reflections, this work engages with Wallace Stevens, Ossip Mandelstam, and Emily Dickinson. In addition to poems Groves gives a supplement of prose, a short essay titled "Affirmation of Instruction." Poetry scholar Judith Balso wrote a foreword in French to the work.